ZnO and Bi-metallic (Ag–Au) Layers Based Surface Plasmon Resonance (SPR) Biosensor with BaTiO3 and Graphene for Biosensing Applications. Issue 2 (17th February 2023) - Mudgal, N.; Saharia, Ankur; Agarwal, Ankit; Singh, G.
Abstract : In this work, a novel design of Zinc Oxide (ZnO) and bi-metallic (Ag–Au) layers based surface plasmon resonance (SPR) biosensor with barium titanate (BaTiO3 ) and graphene is proposed. The proposed structure consists of SF10 glass prism, ZnO, Ag, Au, BaTiO3, and graphene as a top layer for biomolecules adsorption. Here, the performance of this structure is studied and analysed for sensitivity along with the accuracy of detection and quality parameter for the shift in refractive index (RI) from 1.33 (sensing medium) to 1.45 and our reported results show that addition of bimetallic (Ag–Au) layers along with BaTiO3, improve the sensitivity of the proposed structure to 14.85% for the same RI range compared to last reported MoS2 -graphene-based SPR sensor. Here at λ = 632.8 nm, maximum sensitivity is reported as 116.67 degree/RIU while the accuracy of detection and the quality parameter are obtained as 4.54 and 37.87 RIU −1 respectively. These high-performance parameters of the design make this structure suitable for biosensing applications.